2012
DOI: 10.1088/1758-5082/5/1/015001
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid printing of mechanically and biologically improved constructs for cartilage tissue engineering applications

Abstract: Bioprinting is an emerging technique used to fabricate viable, 3D tissue constructs through the precise deposition of cells and hydrogels in a layer-by-layer fashion. Despite the ability to mimic the native properties of tissue, printed 3D constructs that are composed of naturally-derived biomaterials still lack structural integrity and adequate mechanical properties for use in vivo, thus limiting their development for use in load-bearing tissue engineering applications, such as cartilage. Fabrication of viabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
353
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 524 publications
(361 citation statements)
references
References 38 publications
4
353
1
3
Order By: Relevance
“…Hydrogels have previously been reinforced with solutionelectrospun nonwovens 9,24,25,27 . However, most traditional solution-electrospun meshes have disadvantages from both a mechanical and biological point of view, for example, fibres are not fused and hence slide under loading meshes are usually not thicker than 100 m and have a pore size of less than 5 mm and are, therefore, too dense for cell infiltration 25,27,40 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogels have previously been reinforced with solutionelectrospun nonwovens 9,24,25,27 . However, most traditional solution-electrospun meshes have disadvantages from both a mechanical and biological point of view, for example, fibres are not fused and hence slide under loading meshes are usually not thicker than 100 m and have a pore size of less than 5 mm and are, therefore, too dense for cell infiltration 25,27,40 .…”
Section: Discussionmentioning
confidence: 99%
“…However, most traditional solution-electrospun meshes have disadvantages from both a mechanical and biological point of view, for example, fibres are not fused and hence slide under loading meshes are usually not thicker than 100 m and have a pore size of less than 5 mm and are, therefore, too dense for cell infiltration 25,27,40 . To overcome these issues related to traditional solution electrospinning, fibres have been collected in an earthed ethanol bath, yielding nonwovens with high porosities 9,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo test using dorsal subcutaneous zone of nude mouse showed that the amounts of collagen fibers and cartilaginous tissue formation of chondrocyte encapsulated PCL/alginate scaffolds with TGF-beta were higher than other control hydrogels. PCL was also used as composite material for cartilage tissue engineering applications [112] . Electrospun PCL and fibrin/collagen hydrogel containing chondrocytes were fabricated layer by layer by hybrid inkjet printing/ electrospinning system.…”
Section: Soft Tissue Engineering Applicationmentioning
confidence: 99%
“…Hybrid of 3D printing and electrospinning is a good example of such a technique. 54,55 This new method can be further considered to simplify the fabrication of novel WSR composites with value-added performance by incorporating of 3D printing with electrospinning process, as shown in Figure 7(d).…”
Section: Future Of Wsrmentioning
confidence: 99%